1992
DOI: 10.1037/0022-3514.63.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism in the former Soviet Union.

Abstract: Two studies examined the relevance of the authoritarian personality in the Soviet Union. In a 1991 Moscow quota sample, authoritarianism strongly predicted support for reactionary leaders and military actions and opposition to democratic and non-Russian leaders and to democratic activities. The positive correlation between authoritarianism and support for Marxist-Leninist ideology was significant but lower than in 1989. Consistent with the theory that conventionalism is a central attribute of authoritarianism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 29 publications
5
112
2
5
Order By: Relevance
“…McFarland et al's (1992) findings also cast doubt on the idea that authoritarianism generally goes along with the endorsement of inequality. Although the authoritarian personalities in Russia were psychologically similar to those in the West, this was not the case regarding inequalities.…”
Section: Empirical Findings From Communist Countriesmentioning
confidence: 96%
See 2 more Smart Citations
“…McFarland et al's (1992) findings also cast doubt on the idea that authoritarianism generally goes along with the endorsement of inequality. Although the authoritarian personalities in Russia were psychologically similar to those in the West, this was not the case regarding inequalities.…”
Section: Empirical Findings From Communist Countriesmentioning
confidence: 96%
“…Moreover, McFarland et al (1992) suggested that the authoritarian personality in the Soviet Union, although procommunist, was psychologically the same as Western authoritarianism. .…”
Section: Empirical Findings From Communist Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further empirical research has shown that some of these characteristics may need to be attributed to both leftand right-wing extreme ideological rigidity, as for instance suggested by findings that in the former Soviet Union, authoritarian tendencies are associated with increase in left-wing orientation (McFarland et al, 1992). Indeed, a recent large-scale sample in the Netherlands reveals that both the left and right extremes are more fearful of socioeconomic developments than political moderates (van Prooijen, Krouwel, Boiten, & Eendebak, 2015).…”
Section: Political Trust and Extreme Political Ideologymentioning
confidence: 99%
“…Research conducted in postsocialist countries shows that conventionality motivation (Hadarics, 2016) and psychological variables related to this kind of motivation, like authoritarianism (Korzeniowski, 2006;McFarland, Ageyev, & Abalakina-Paap, 1992;Todosijević, 2008), need for closure (Golec, 2002;Kossowska & Van Hiel, 2003), or conservation values (Duriez, Van Hiel, & Kossowska, 2005) endorse the acceptance of paternalistic and egalitarian economic attitudes and beliefs, because these are the ideological elements in this region that can provide the feeling of certainty and predictability by their normative nature.…”
Section: Introductionmentioning
confidence: 99%